Dynamic shear response of ultra-high-performance fiber-reinforced concretes under impact loading. (July 2022) - Tran, Ngoc Thanh; Nguyen, Duy Liem; Vu, Quoc Anh; Kim, Dong Joo; Ngo, Tri Thuong
Abstract: Ultra-high-performance fiber-reinforced concrete (UHPFRC) is known as an advantageous material for enhancing the shear response capacity of structures subjected to extreme loads, such as in cases of missile strikes, terrorist attacks, or earthquakes. However, there is limited information on the shear response of UHPFRC, especially at high strain rates. In this study, the shear strength, shear strain capacity, and shear peak toughness of UHPFRCs with three fiber types, i.e., twisted fiber (LT), hooked fiber (LH), and smooth fiber (LS), were investigated at static and at high strain rates (up to 245 s −1 ). The results indicated all UHPFRCs exhibited shear strain hardening behavior accumulated to multiple microcracks at both static and high strain rates although their shear responses were found to be strongly dependent on the fiber type. Among the investigated fiber types, the LT fibers produced the highest shear resistance in terms of shear strength, shear strain capacity, and shear peak toughness at static rates, whereas LS fibers did at high strain rates. The LS fibers exhibited the highest strain rate sensitivity of shear resistance, followed by the LH and LT fibers. Unlike LS fibers, LH and LT fibers showed fiber breakage during the shear loading process at high strain rates. Based on the experimental results, empirical equations to predict the dynamic increase factor (DIF) of shear strength of UHPFRCs at high strain rates were also proposed.